PERAN ZAKAT PRODUKTIF DALAM UPAYA PENANGGULANGAN KEMISKINAN DENGAN PENDEKATAN MODEL CIBEST - Abu, Rahma Rafifah; Mongkito, Abdul Wahid; Toar, Alfian (IAIN Kendari, 2023)
This study aims to examine the impact of productive Zakat on poverty reduction in Kendari City using the CIBEST model. The research addresses two main questions: (1) What is the distribution model of productive Zakat for poverty alleviation at BAZNAS Kendari City (2) What are the effects on recipients (mustahiq) after receiving productive zakat assistance from BAZNAS Kendari City using the CIBEST model. The research adopts a qualitative, descriptive approach, collecting data through interviews, observation, and documentation. The findings indicate that: (1) The productive zakat distribution model focuses on planning, organizing, and implementation stages, with limited supervision due to human resource constraints. (2) Using the CIBEST Model, changes in mustahiq households were observed before and after receiving productive Zakat. Notably, the number of prosperous households increased from 14 to 22 in Quadrant I, while material poverty decreased from 8 to 6 households in Quadrant II. Spiritual poverty decreased from 8 to 2 households in Quadrant III, and no households fell into the absolute poverty category in Quadrant IV, both before and after receiving productive Zakat.